Five Year Outcomes of Surgical Treatment for Popliteal Artery Entrapment Syndrome. Issue 4 (April 2016) - Lejay, A.; Delay, C.; Georg, Y.; Gaertner, S.; Ohana, M.; Thaveau, F.; Lee, J.T.; Geny, B.; Chakfe, N.
Abstract : Objective/Background: The aim of this study was to evaluate long-term outcomes following surgery for popliteal artery entrapment syndrome. Methods: A retrospective study of all patients that underwent surgery for popliteal artery entrapment syndrome between January 2003 and December 2009 was performed. Patient demographic data, clinical features, imaging modalities, and surgical management were recorded. The primary outcome was 5 year patency. Results: Eighteen patients (25 limbs) underwent surgery. The mean age at the time of surgical procedure was 35 (median 35 years; range 15–49). Presentation was bilateral in seven patients (39%). Diagnosis was made using various imaging modalities, including position stress test, Duplex ultrasonography, computed tomography angiography, magnetic resonance imaging and conventional angiography. In four limbs the popliteal artery was compressed and undamaged (16%), and treatment consisted of musculo-tendinous division alone. In 16 limbs the popliteal artery was damaged with lesions limited to the popliteal artery (64%) where treatment consisted of venous interposition. In five limbs lesions extended beyond the popliteal artery (20%) and procedures included one below knee femoro-popliteal bypass, three femoro-posterior tibial bypasses, and one popliteo-posterior tibial bypass. Musculo-tendinous division was associated with vascular reconstruction in 19 limbs (90%). Mean follow up was 82 months (median 81 months, range 60–120). Five year patency was 84%. Conclusion: Long-term outcomes of surgical procedures performed for popliteal artery entrapment syndrome can be considered satisfactory.